On the Formation and Structure of International Exchanges - Matthew J. Clayton; Bjorn N. Jorgensen; Kenneth A. Kavajecz (Tinbergen Institute, 1999)
We investigate the formation and structure of 248 financial exchangesthroughout the world. First, we empirically analyze the determinantsof exchange formation as well as the impact of exchange formation onthe domestic country's economy. Second, conditional on formation, weuse a probit model to relate the choice of trading mechanism to thecharacteristics of the economic environment in which the exchangeexists. We find that the main determinants of exchange formation in acountry are the degree of economic freedom, the size of the economy,the availability of technology, and the legal system. In addition, wefind that the impact of exchange formation on the macro economy islimited to a reduction in the growth of the monetary aggregates withno significant impact on productivity. Lastly, our results show thatthe choice if trading mechanism depends on the country's economicdevelopment, the degree of competition, and the extent of economicfreedom.
Keywords: 330; Internationaler Zahlungsverkehr; Internationaler Finanzmarkt; Welt